Targeted Transcriptional Profiling of Microdissected Biopsy Specimens Representing Early Colonic Neoplasia. Issue 12 (12th July 2016) - Mo, Allen; Jackson, Stephen; Devers, Thomas J.; Rosenberg, Daniel W.
ABSTRACT: Our incomplete understanding of the critical changes that accompany the earliest stages of tumor initiation provides a substantial hurdle for the development of novel intervention strategies for cancer prevention. Premalignant lesions are inherently difficult to characterize given their diminutive size, creating technical obstacles for accurate genetic profiling. Here, we describe an approach combining laser‐capture microdissection (LCM) with targeted RNA‐sequencing to study the transcriptional state of epithelial and stromal cells during the earliest detectable stage of human colorectal neoplasia, the aberrant crypt foci (ACF). We provide a robust and reproducible workflow for RNA isolation, library preparation, and expression profiling of laser‐captured cells from frozen OCT‐embedded tissue specimens. It is anticipated that the methodological approach outlined in this report will provide a framework for a broad range of microgenomics analyses that can be routinely applied to many other premalignant tissues. J. Cell. Biochem. 117: 2677–2681, 2016. © 2016 Wiley Periodicals, Inc.